Case studies in elementary and secondary curriculum - Boboc, Marius; Nordgren, R. D., 1960-; Sage eBooks (London : SAGE, 2010)
'Case Studies in Elementary and Secondary Curriculum' provides 21 real-world cases that provide the opportunity for educators to explore the different perspectives that different stakeholders take on the concept of curriculum.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Education, Elementary -- Curricula -- Case studies; Education, Secondary -- Curricula -- Case studies; Electronic books